2017
DOI: 10.1038/cddis.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 4 coordinates glial membrane recruitment and phagocytic clearance of degenerating axons in Drosophila

Abstract: Neuronal damage induced by injury, stroke, or neurodegenerative disease elicits swift immune responses from glial cells, including altered gene expression, directed migration to injury sites, and glial clearance of damaged neurons through phagocytic engulfment. Collectively, these responses hinder further cellular damage, but the mechanisms that underlie these important protective glial reactions are still unclear. Here, we show that the evolutionarily conserved trimeric protein phosphatase 4 (PP4) serine/thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Studies of normal cell migration and tumor cell invasion demonstrate that MMP-1 expression influences actin remodeling during cell movement ( Rudrapatna et al, 2014 ). We have also previously shown that antennal nerve injury induces striking cytoskeletal remodeling, which requires activity of the protein phosphatase 4 (PP4) complex and likely also the Rho GTPase Rac1 in responding glia ( Winfree et al, 2017 ). To determine how glial MMP-1 influences actin polymerization and cytoskeletal remodeling in response to axon injury, we stained control and glial MMP-1 RNAi brains with phalloidin-TRITC, which selectively binds filamentous actin ( Wulf et al, 1979 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of normal cell migration and tumor cell invasion demonstrate that MMP-1 expression influences actin remodeling during cell movement ( Rudrapatna et al, 2014 ). We have also previously shown that antennal nerve injury induces striking cytoskeletal remodeling, which requires activity of the protein phosphatase 4 (PP4) complex and likely also the Rho GTPase Rac1 in responding glia ( Winfree et al, 2017 ). To determine how glial MMP-1 influences actin polymerization and cytoskeletal remodeling in response to axon injury, we stained control and glial MMP-1 RNAi brains with phalloidin-TRITC, which selectively binds filamentous actin ( Wulf et al, 1979 ).…”
Section: Resultsmentioning
confidence: 99%
“…The current study adds Dynamin-dependent glial phagocytosis roles during critical period remodeling in late-stage circuit refinement in a healthy brain. Draper likewise has well-established roles in glial phagocytosis in both mammals and Drosophila 3 , 35 , 37 . In Drosophila , Draper has been extensively studied in the context of neuronal injury, with the receptor binding to cellular debris and/or neural ligands activating a well-characterized signaling cascade leading to Dynamin-dependent internalization 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that calcium increases in DRG following a regeneration‐competent sciatic but not a regeneration‐incompetent spinal injury to activate PP4c that is required for HDAC3 dephosphorylation. While PP4 has been shown to play a role in phagocytic clearance of degenerating axons in Drosophila (Winfree et al , ), its role in axonal regeneration remained unexplored so far. Similarly, while calcium has been linked to the activation of multiple signalling pathways in injured axons, it was previously unknown whether a central spinal lesion associated with regenerative failure would fail to trigger significant increases in calcium in the DRG cell bodies.…”
Section: Discussionmentioning
confidence: 99%